Hatchery selection may depress the number of motile sperm but intensify selection for their swimming velocity in the Arctic charr - Kekäläinen, Jukka; Figenschou, Lars; Janhunen, Matti; Kortet, Raine; Peuhkuri, Nina; Rudolfsen, Geir (Aquaculture International, 2012)
The ability of captive breeding programs to maintain genetic diversity and fitness has often been questioned. Recent studies suggest that fitness loss can be extremely rapid in various traits, but it is poorly known how captive breeding affects sperm quality and thus male fertility. We studied the potential effects of hatchery-induced selection on traits indicative of semen quality, in four generations of captive bred Arctic charr Salvelinus alpinus L. We found that the number of motile sperm cells decreased, but that the swimming velocity of the sperm increased over generations. The independent effects of inbreeding and hatchery selection on semen traits could not be separated, but since in small captive broodstocks, both of them often act together, the present results should indicate real changes of semen traits in such situations. Taken together, the present data suggest that the fitness loss in some semen traits (number of motile sperm) can be extremely rapid, but selection on other, closely related traits (swimming velocity) may delay or counteract the overall deterioration of male fertilizing ability during captivity.